Holding device

JP7639050B2Active Publication Date: 2025-03-04NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023067631
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-03-04
Estimated Expiration
2043-04-18

AI Technical Summary

Benefits of technology

【0012】 (4)上記形態の保持装置において、前記接着剤層を、高周波誘導結合プラズマ(ICP)を光源とするICP発光分析法により定量分析したリン(P)の量が100ppm以上であってもよい。このようにすると、リン(P)のラジカルトラップ効果により、接着剤の分解を抑制することができるため、接着剤層の耐熱性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639050000001
    Figure 0007639050000001
  • Figure 0007639050000002
    Figure 0007639050000002
  • Figure 0007639050000003
    Figure 0007639050000003
Patent Text Reader

Abstract

To provide a technique capable of suppressing peeling or breaking of an adhesive layer in a holding device that holds an object.SOLUTION: A holding device comprises: a plate-like part formed in a plate shape; a base part that supports the plate-like part and is formed in the plate shape; and an adhesive agent layer that is arranged to between the plate-like part and the base part, contains an adhesive agent and an inorganic filler, and bonds the plate-like part and the base part. The adhesive agent layer satisfies the following equation of |(γ1-γ0) / γ0|≤0.15. Here, γ0 is a shearing strain of the adhesive agent layer before heating, and γ1 is a shearing strain after the heating of the adhesive agent layer for 3000 hours at 180°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a retention device. [Background technology]

[0002] As a holding device for holding an object, for example, an electrostatic chuck for holding an object such as a wafer during semiconductor manufacturing is known. The electrostatic chuck generally includes a plate-shaped portion on which the object is placed, a base portion for supporting the plate-shaped portion, and an adhesive layer for bonding the plate-shaped portion and the base portion.

[0003] The electrostatic chuck is often used in an environment where the temperature is changed, for example, during processing of a wafer. In this case, if there is a large difference in the thermal expansion coefficient between the plate-like part and the base part, a large thermal stress is applied to the electrostatic chuck, causing a problem that the adhesive layer may peel off or break.

[0004] To address this problem, a technology has been proposed in which the adhesive layer has an elongation rate of 100% or more and a Shore A hardness of 70 or less, thereby improving the elasticity and flexibility of the adhesive layer and making the adhesive layer less likely to peel off even when the electrostatic chuck is used in conditions where temperature changes are repeated (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-207374 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when the heat input to the plate-shaped portion increases, such as when the electrostatic chuck is used while being exposed to a higher-power plasma, peeling or breakage of the adhesive layer may occur even with the technique described in Patent Document 1. Note that these problems are not limited to electrostatic chucks, but are common to various holding devices, such as semiconductor manufacturing devices, such as plasma etching devices.

[0007] The present disclosure has been made to solve at least part of the above-mentioned problems, and aims to provide a technology that suppresses peeling or breakage of an adhesive layer in a holding device that holds an object. [Means for solving the problem]

[0008] The present disclosure can be realized in the following forms. (1) According to one embodiment of the present disclosure, there is provided a holding device for holding an object. The holding device includes a plate-shaped portion, a base portion formed in a plate shape and supporting the plate-shaped portion, and an adhesive layer disposed between the plate-shaped portion and the base portion, containing an adhesive and an inorganic filler, and bonding the plate-shaped portion and the base portion, the adhesive layer satisfying |(γ1-γ0) / γ0|≦0.15. Here, γ0 is the shear strain of the adhesive layer before heating, and γ1 is the shear strain of the adhesive layer after heating at 180° C. for 3000 hours.

[0009] According to the holding device of this embodiment, the shear strain of the adhesive layer satisfies |(γ1-γ0) / γ0|≦0.15, so that the adhesive layer is less likely to deteriorate when used at high temperatures (180°C). In other words, the adhesive layer has excellent heat resistance. Therefore, even when the holding device is used at high temperatures of about 180°C, peeling or breakage of the adhesive layer can be suppressed.

[0010] (2) In the holding device of the above embodiment, the adhesive layer may satisfy |(γ2-γ0) / γ0|≦0.2. Here, γ0 is the shear strain of the adhesive layer before heating, and γ2 is the shear strain of the adhesive layer after heating at 200°C for 3000 hours. With this configuration, it is possible to reduce deterioration of the adhesive layer when used at high temperatures (200°C). Since the heat resistance of the adhesive layer can be further improved, peeling or breakage of the adhesive layer can be suppressed even when the holding device is used at an even higher temperature of about 200°C.

[0011] (3) In the holding device of the above embodiment, the adhesive may be a silicone-based resin. Silicone-based resins have better heat resistance and flexibility than other resins such as epoxy resins, fluororesins, and acrylic resins, and such a configuration can provide an adhesive layer that is more heat-resistant, flexible, and has stress relaxation properties. As a result, peeling and breakage of the adhesive layer can be further suppressed.

[0012] (4) In the holding device of the above embodiment, the amount of phosphorus (P) in the adhesive layer, as determined by quantitative analysis using inductively coupled plasma (ICP) emission spectrometry using a high-frequency inductively coupled plasma (ICP) as a light source, may be 100 ppm or more. In this way, the decomposition of the adhesive can be suppressed due to the radical trapping effect of phosphorus (P), thereby improving the heat resistance of the adhesive layer.

[0013] (5) In the holding device of the above embodiment, the adhesive layer may contain 30% by volume or more of the inorganic filler. In this way, the inorganic filler prevents a crosslinking reaction of the resin (adhesive), so that the adhesive layer can maintain its softness even at high temperatures and the heat resistance can be improved.

[0014] The present disclosure may be realized in various forms other than those described above, for example, in the form of a semiconductor manufacturing apparatus including a holding device, a manufacturing method for a holding device, a method for forming a joint, and the like. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is an explanatory diagram illustrating a schematic configuration of an electrostatic chuck. [Diagram 2] FIG. 2 is an explanatory diagram illustrating a cross-sectional configuration of the electrostatic chuck. [Diagram 3] FIG. 1 is a diagram showing the specifications of a sample. [Figure 4] FIG. 1 is an explanatory diagram illustrating a method for calculating shear strain. [Diagram 5] FIG. 1 is a graph showing the rate of change in shear strain due to heating at 180° C. [Figure 6] FIG. 13 is a graph showing the rate of change in shear strain due to heating at 200° C. [Figure 7] FIG. 13 is a graph showing the change in the rate of change of shear strain of Sample 1 versus heating time. [Figure 8] FIG. 13 is a graph showing the change in the rate of change of shear strain of Sample 2 with respect to heating time. [Figure 9] FIG. 13 is a graph showing the change in the rate of change of shear strain of Sample 3 versus heating time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] A. Embodiment: (A-1) Overall structure of electrostatic chuck: FIG. 1 is an explanatory diagram that shows a schematic configuration of an electrostatic chuck 10 in an embodiment. FIG. 2 is an explanatory diagram that shows a schematic cross-sectional configuration of the electrostatic chuck 10. In FIG. 1, a part of the electrostatic chuck 10 is cut away. In addition, in the figure, mutually orthogonal X, Y and Z axes are shown in order to specify the direction. In this specification, for convenience, the positive direction of the Z axis is referred to as the upward direction, and the negative direction of the Z axis is referred to as the downward direction, but the electrostatic chuck 10 may actually be installed in a direction different from such an orientation. The X axis, Y axis and Z axis shown in each figure each indicate the same direction. Note that each of the above figures shows the arrangement of each part typically, and does not accurately show the ratio of the dimensions of each part.

[0017] The electrostatic chuck 10 is a device that attracts and holds an object by electrostatic attraction, and is used, for example, to fix an object, that is, a wafer W (FIG. 2), in a vacuum chamber of a semiconductor manufacturing device. The electrostatic chuck 10 includes a plate-shaped portion 20, a base portion 30, and an adhesive layer 40. These are layered in the order of the plate-shaped portion 20, the adhesive layer 40, and the base portion 30 toward the -Z axis direction (vertically downward). The electrostatic chuck 10 in this embodiment is also referred to as a "holding device."

[0018] The plate-shaped portion 20 is a substantially circular plate-shaped member having a first surface 24 on which an object is placed and a second surface 26 that is the reverse side of the first surface 24, and is formed mainly from ceramic (e.g., aluminum oxide, aluminum nitride, etc.). In this specification, when a specific component is "the main component" or "the main material forming the specific component", it means that the content of the specific component is 50 volume % or more. In other embodiments, the plate-shaped portion 20 may be formed mainly from a material other than ceramic, such as a resin such as polyimide.

[0019] As shown in FIG. 2, an adsorption electrode 22 is disposed inside the plate-shaped portion 20. The adsorption electrode 22 is formed of a conductive material such as tungsten or molybdenum. When a voltage is applied to the adsorption electrode 22 from a power source (not shown), an electrostatic attraction is generated, and the wafer W is adsorbed and fixed to the first surface 24 of the plate-shaped portion 20 by this electrostatic attraction. The adsorption electrode 22 may be of a bipolar type or a unipolar type. In addition, a heater electrode (not shown) may be provided inside the plate-shaped portion 20, which is composed of a resistance heating element formed of a conductive material (such as tungsten or molybdenum) and is used to heat the wafer W adsorbed and fixed to the first surface 24.

[0020] The base portion 30 is a plate-like member that is disposed on the second surface 26 side of the plate-like portion 20, supports the plate-like portion 20, has a cooling function, and is formed in a substantially circular shape. The base portion 30 may contain at least one metal selected from the group consisting of aluminum, magnesium, molybdenum, titanium, tungsten, and nickel. Among the above-mentioned metals, molybdenum, titanium, and tungsten have relatively small coefficients of thermal expansion, and therefore, when the base portion 30 is constructed using at least one of these metals, it is desirable to suppress the difference in coefficient of thermal expansion between the base portion 30 and the plate-like portion 20. In this specification, the term "coefficient of thermal expansion" refers to the "coefficient of linear expansion." Furthermore, since magnesium has a relatively small Young's modulus, when the base portion 30 is constructed using magnesium, it is desirable to reduce the thermal stress generated in the base portion 30. Furthermore, aluminum has a relatively high thermal conductivity, is easy to process, and is low in cost. Therefore, when the base portion 30 is constructed using aluminum, it is desirable to increase the cooling efficiency of the plate-like portion 20 and the wafer W by the base portion 30 and suppress the manufacturing cost of the electrostatic chuck 10. From the viewpoint of suppressing manufacturing costs while increasing the cooling efficiency of the base portion 30, it is desirable for the base portion 30 to have a high metal content, and it is desirable for the base portion 30 to be mainly composed of metal. For example, it is desirable for the base portion 30 to contain 90 mass % or more of highly versatile aluminum (for example, to be made of an aluminum alloy such as A6061 or A5052). However, the base portion 30 may contain components other than metal, such as ceramic.

[0021] A plurality of coolant channels 32 are formed inside the base portion 30 along the XY plane. The base portion 30 is cooled by flowing a coolant such as a fluorine-based inert liquid, water, or liquid nitrogen through the coolant channels 32. The plate-shaped portion 20 is cooled by heat transfer between the base portion 30 and the plate-shaped portion 20 via the adhesive layer 40, and the wafer W held on the first surface 24 of the plate-shaped portion 20 is cooled. This realizes temperature control of the wafer W. In addition to the form having the coolant channels 32 inside the base portion 30, the base portion 30 may be given a cooling function by cooling the base portion 30 from the outside of the base portion 30. Furthermore, the base portion 30 may not have a cooling function. When the base portion 30 does not have a cooling function, the electrostatic chuck 10 may have a configuration for cooling the plate-shaped portion 20 from the outside.

[0022] The adhesive layer 40 is disposed between the plate-shaped portion 20 and the base portion 30 to bond the plate-shaped portion 20 and the base portion 30. The adhesive layer 40 contains an adhesive formed of a resin material and an inorganic filler. The adhesive layer 40 will be described in detail later.

[0023] The electrostatic chuck 10 further includes a plurality of gas supply paths 50. The gas supply paths 50 are provided penetrating the plate-shaped portion 20, the adhesive layer 40, and the base portion 30 in the Z direction, and open at gas discharge ports 52 formed on the first surface 24 (see FIG. 1). The gas supply paths 50 receive an inert gas, such as helium gas, from a gas supply device (not shown), and supply the inert gas from the gas discharge ports 52 to the space between the first surface 24 and the wafer W. This improves the heat transfer between the plate-shaped portion 20 and the wafer W, and further improves the controllability of the temperature distribution of the wafer W. The gas supply paths 50 are not essential, and the electrostatic chuck 10 may not be provided with the gas supply paths 50.

[0024] (A-2) Composition of adhesive layer: The adhesive layer 40 of the electrostatic chuck 10 of this embodiment satisfies |(γ1-γ0) / γ0|≦0.15, where γ0 is the shear strain of the adhesive layer before heating, and γ1 is the shear strain of the adhesive layer after heating at 180° C. for 3000 hours. The shear strain is the strain that occurs when a shear force is applied to the adhesive layer 40 to break it, and is calculated by the following formula (1). Shear strain γ (%) = displacement in the direction of shear force / thickness of adhesive layer 40 × 100 (1) A specific measurement method using a tensile tester for measuring the shear strain will be described in detail later. When the adhesive layer 40 is heated to 180°C, the rate of change in shear strain before and after heating is small, and the adhesive layer 40 is little deteriorated by heating. In other words, the adhesive layer 40 is little deteriorated when used at a high temperature (180°C) and has excellent heat resistance. Therefore, even when the electrostatic chuck 10 is used at a high temperature of about 180°C, peeling or breakage of the adhesive layer 40 can be suppressed.

[0025] The adhesive layer 40 preferably further satisfies |(γ2-γ0) / γ0|≦0.2. Here, γ0 is the shear strain of the adhesive layer before heating, and γ2 is the shear strain of the adhesive layer after heating at 200° C. for 3000 hours. In this way, it is possible to reduce deterioration of the adhesive layer when it is used at a high temperature (200° C.). Since the heat resistance of the adhesive layer can be further improved, peeling or breakage of the adhesive layer 40 can be suppressed even when the electrostatic chuck 10 is used at an even higher temperature of about 200° C.

[0026] The adhesive contained in the adhesive layer 40 may be, for example, a silicone resin, an epoxy resin, a fluororesin, an acrylic resin, or the like. Silicone resin is preferable because it has relatively excellent heat resistance and flexibility. Silicone resin has a relatively low elastic modulus, and therefore has a high function of alleviating thermal stress generated in the adhesive layer 40. Therefore, peeling or breakage of the adhesive layer 40 can be further suppressed.

[0027] As the inorganic filler, granular or powdery substances made of various inorganic materials including ceramics, metal oxides, metals, or other inorganic compounds can be used. Specifically, as the inorganic filler, for example, aluminum nitride (AlN), aluminum oxide (alumina: Al2O3), zirconium oxide (zirconia: ZrO2), yttrium oxide (yttria: Y2O3), yttrium fluoride (YF3), silicon carbide (SiC), silicon nitride (Si3N4), silicon dioxide (silica: SiO2), iron oxide, barium sulfate, calcium carbonate, etc. can be used. Since the above-mentioned inorganic materials constituting the inorganic filler generally have a higher thermal conductivity than the resin that is the adhesive, adding the inorganic filler to the adhesive can increase the thermal conductivity in the adhesive layer 40. In particular, from the viewpoint of having a relatively high thermal conductivity and being easy to suppress the thermal resistance of the adhesive layer 40, aluminum nitride, aluminum oxide, and silicon carbide are preferable as materials constituting the inorganic filler, and aluminum nitride and aluminum oxide are particularly preferable.

[0028] One of the degradation processes of an adhesive formed from a resin material is a process in which the adhesive hardens and loses flexibility as a result of the progress of a crosslinking reaction. By including an inorganic filler in the adhesive layer 40, the movement of radicals is hindered and the radicals are deactivated before they reach other molecules, so that the above-mentioned crosslinking reaction is suppressed and the deterioration of the adhesive can be suppressed. In other words, when the adhesive layer 40 is exposed to high temperatures, the deterioration of the adhesive layer 40 can be suppressed. In other words, the heat resistance of the adhesive layer 40 can be improved.

[0029] The adhesive layer 40 may further contain a catalyst for accelerating the curing reaction, a silane coupling agent for accelerating the curing and adhesion to impart adhesiveness, a crosslinking agent, a reaction inhibitor for adjusting the curing speed of the adhesive, or a viscosity modifier. As the catalyst contained in the adhesive layer 40, various conventionally known catalysts can be used, such as a platinum catalyst, a rhodium catalyst, a titanium catalyst, a bismuth catalyst, etc. Among them, it is preferable to use a platinum catalyst, which has high reactivity. There is no particular restriction on the silane coupling agent contained in the adhesive layer 40, and it can be appropriately selected from conventionally known silane coupling agents, such as those having any of a vinyl group, an epoxy group, a methacryl group, an amino group, a mercapto group, and an isocyanate group as an organic reactive group. In addition, a titanate-based coupling agent or an aluminate-based coupling agent may be used instead of the above silane coupling agent. As the crosslinking agent contained in the adhesive layer 40, an organohydrogenpolysiloxane having at least three hydrosilyl groups in one molecule can be used. More specifically, for example, at least one of polymethylhydrogensiloxane and poly(dimethylsiloxane-methylhydrogensiloxane) can be used.

[0030] As the reaction inhibitor contained in the adhesive layer 40, various conventionally known reaction inhibitors can be used, for example, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, triallyl isocyanurate, etc. As the viscosity modifier contained in the adhesive layer 40, various conventionally known viscosity modifiers can be used, for example, fumed silica, fumed silica, colloidal silica, fumed alumina, fumed alumina, colloidal alumina, etc. The types and amounts of the above-mentioned catalysts, silane coupling agents, crosslinking agents, reaction inhibitors, viscosity modifiers, etc. may be appropriately selected depending on, for example, the type of resin constituting the adhesive layer 40, etc.

[0031] The amount of phosphorus (P) quantitatively analyzed by ICP emission spectrometry using high-frequency inductively coupled plasma (ICP) as a light source for the adhesive layer 40 may be 100 ppm or more. Adhesives formed from resin materials generate radicals during the process of decomposition due to heat. When the radicals move and decompose other molecules, the decomposition of the entire resin progresses and the adhesive deteriorates. Therefore, by trapping and deactivating the radicals midway, the decomposition of the resin can be suppressed and the heat resistance of the adhesive layer can be improved. If the adhesive layer 40 contains phosphorus (P), the heat resistance of the adhesive layer 40 can be improved due to the radical trapping effect of phosphorus (P).

[0032] For example, phosphorus (P) can be contained in the adhesive layer 40 by using an inorganic filler that has been treated with phosphoric acid. For example, surface-coated aluminum nitride particles having a coating layer made of aluminum phosphate are produced by subjecting aluminum nitride particles to phosphoric acid treatment. The phosphoric acid treatment can be, for example, a treatment in which an inorganic phosphoric acid compound is dropped into a dispersion liquid in which aluminum nitride particles are dispersed in a solvent, and the mixture is reacted under a temperature condition of about room temperature to 80°C, and then the solvent is volatilized. The inorganic phosphoric acid compound used can be, for example, phosphoric acid (orthophosphoric acid: H3PO4), pyrophosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, metaphosphoric acid, and mixtures thereof. The phosphoric acid treatment can also be a treatment in which a solution in which an organic phosphoric acid compound known as an antioxidant or antiaging agent is dissolved is dropped into a dispersion liquid in which aluminum nitride particles are dispersed in a solvent, and then the solution is evaporated to dryness, and then the solution is heated under a temperature condition of 150 to 800°C.Examples of the organic phosphoric acid compound include tris(2,4-di-tert-butylphenyl)phosphite (CAS registration number: 31570-04-4), 3,9-dioctadecan-1-yl-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (CAS registration number: 3806-34-6), 3,9-bis(2,4-di-tert-butylphenoxy)-2,4, 8,10-Tetraoxa-3,9-diphosphaspiro[5.5]undecane (CAS Registry Number: 26741-53-7), 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (CAS Registry Number: 80693-00-1), 3,9-bis[2,4-bis(1-methyl-1-phenyl 2,4,8,10-Tetra-tert-butyl-6-[(2-ethylhexyl)oxy]-12H-dibenzo[d,g][1,3,2]dioxaphosphocin (CAS Registry Number: 126050-54-2), bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite (CAS Registry Number: 145650-60-8), reaction products of biphenyl, 2,4-di-tert-butylphenol and phosphorus trichloride (synonym: tetrakis[(2,4-di-t-butylphenyl)-1,1-biphenyl]-4-4'diylbisphosphonite, CAS Registry Number: 119345-01-6), etc. As organic antioxidants, there are phenol-based antioxidants, sulfur-based antioxidants, and amine-based antioxidants, but phosphoric acid-based antioxidants are more preferable than phenol-based antioxidants because the antioxidant itself has high heat resistance, and phosphoric acid-based antioxidants are more preferable than sulfur-based antioxidants and amine-based antioxidants because they do not cause curing inhibition of silicone resins.

[0033] The adhesive layer 40 may contain 30% by volume or more of inorganic filler, preferably 40% by volume or more, and more preferably 45% by volume or more. In this way, the inorganic filler prevents the crosslinking reaction of the resin (adhesive), so that the adhesive layer 40 can maintain its softness even at high temperatures and improve its heat resistance. The inorganic filler may include the various inorganic fillers described above, and may include inorganic fillers that have been partially treated with phosphoric acid. It is more preferable to contain 30% by volume or more of inorganic fillers that have been treated with phosphoric acid.

[0034] The content (volume %) of the inorganic filler contained in the adhesive layer 40 can be obtained by the following method: The adhesive layer 40 is cross-sectionally processed with a cross-section polisher (CP), and the volume ratio of the inorganic filler is calculated from a cross-sectional SEM (Scanning Electron Microscope) image. EXAMPLES

[0035] The retaining device of the present disclosure will be described below based on examples. Here, sheet-like samples 1 to 3 were produced as samples corresponding to adhesive layers in which the adhesive was a silicone adhesive and the type of inorganic filler was changed.

[0036] <Preparation of each sample> [Preparation of sheet-like samples] FIG. 3 is a diagram showing the specifications of the samples. As shown in the figure, sample 1 uses aluminum nitride (AlN) as the inorganic filler, and samples 2 and 3 use alumina (Al2O3). In sample 1, the inorganic filler is subjected to phosphoric acid treatment, and in samples 2 and 3, the inorganic filler is not subjected to surface treatment. The content of the inorganic filler in samples 1 to 3 is 45 volume % (vol.%). The content (vol.%) of the inorganic filler shown in FIG. 3 was calculated from the above-mentioned cross-sectional SEM image. Three points were observed in the cross-sectional SEM image at a measurement magnification of 1000 times, and the calculation was performed by binarizing the image.

[0037] In each sample, a silicone resin was used as the adhesive. Specifically, either polydimethylsiloxane or polydimethylsiloxane containing 5 mol % of phenyl groups was used as the adhesive material (resin material) before curing. Specifically, samples 1 and 3 used polydimethylsiloxane containing 5 mol % of phenyl groups, and sample 2 used polydimethylsiloxane. Samples 1 to 3 did not contain any inorganic fillers other than the inorganic fillers shown in FIG. 3.

[0038] The sheet-like sample was prepared as follows. The inorganic filler and the silicone resin were mixed to prepare a paste-like adhesive. There is no particular restriction on the mixing method, and mixing with a known stirring blade, a three-roller, a kneader, a rotation-revolution mixer, a planetary mixer, and the like can be used. The prepared paste-like adhesive can be spread on a film with releasability using a known coating device, and cured to obtain a sheet-like sample. For example, a roll coater, a bar coater, a die coater, a knife coater, and the like can be used as the coating device. For example, a polyethylene terephthalate (PET) film can be used as the film with releasability, and a PET film coated with a release agent may be used to enhance releasability. In order to obtain a thick cured product that is difficult to mold with the various coating devices described above, or a block-like cured product, the adhesive may be placed in a container of a specified size and then cured. A container made of polytetrafluoroethylene (PTFE) is preferable because it is easy to remove. Heating may be used for curing as necessary.

[0039] <Evaluation> Rate of change of shear strain Using each of the above samples, the rate of change in shear strain before and after heating was examined. The shear strain (%) was measured by a tensile test using a known tensile tester (Shimadzu Corporation Autograph AGS-5kNX). Measurement sample (adhesive sheet) size: 12.5 x 12.5 mm

[0040] FIG. 4 is an explanatory diagram showing a schematic diagram of a method for calculating shear strain. FIG. 4(A) shows the state of the tensile test as seen from the front, and FIG. 4(B) and FIG. 4(C) show the state as seen from the side. Also, FIG. 4(A) and FIG. 4(B) show the state at the start of the test, and FIG. 4(C) shows the state after the start of the test. The test piece 70 was prepared by attaching the semi-cured adhesive sheet of each sample to a 12.5 mm×12.5 mm portion of two aluminum plates 80, each having a width of 12.5 mm, a length of 100 mm, and a thickness of 1 mm, from the end to a position of 12.5 mm, and bonding the two aluminum plates 80 in a direction in which they can be pulled in opposite directions, heating them at 100° C. for 10 hours, and further heating them at 150° C. for 50 hours to bond them. The thickness t of the test piece 70 at the start of the test is 200 μm.

[0041] Next, the two aluminum plates 80 were held by a tensile test tool and moved relative to each other so that a shear force was applied to the test piece. Here, a tensile tester was used to move one of the aluminum plates in one direction parallel to the adhesive surface at a tensile speed of 2 mm / min, while measuring the strain amount δ as the moving distance (see FIG. 4(C)). A tensile tester and a tool having a sufficiently high rigidity were used, and the moving distance (tensile stroke) of the tool of the tensile tester was taken as the strain amount δ. In FIG. 4(B), the direction of the relative movement of the two aluminum plates is shown by a hollow arrow. Such relative movement of the two aluminum plates was continued until the test piece 70 broke, and the strain amount δ (unit: mm) at the time of breakage was divided by the thickness of the adhesive layer at the time of breakage (unit: mm) to calculate the shear strain (%) of the test piece 70. The distance between the tools (grips) was used as the thickness of the adhesive layer.

[0042] In addition, when measuring the shear strain amount (unit: mm) of the joint part already assembled in the electrostatic chuck, for example, it is performed as follows. First, the joint part is cut out together with the adherend (plate part and base part) by a processing method such as laser cutting. The shape of the cut-out test piece may be such that it can be held by the jig of the tensile tester and the two joined adherends can be pulled in the opposite directions as shown in FIG. 9. Before the tensile test, the area of ​​the joint part and the thickness of the joint part in the cut-out test piece are measured. Thereafter, a tensile test is performed in the same manner as described above to measure the amount of strain. In addition, the electrostatic chuck is not limited to a new one, and a used one can also be used. The electrostatic chuck is obtained before heating, and the rate of change of the shear strain can be confirmed by heating for, for example, 3000 hours.

[0043] [Evaluation Results] The rate of change in shear strain before and after heating was investigated using each of the above samples. For heating temperatures of 180°C and 200°C, the heating time was changed to 0 hours, 500 hours, 1000 hours, 2000 hours, 3000 hours, 5000 hours, 8000 hours, and 10000 hours. For the heating time of 0 hours, the shear strain was measured at room temperature using an unheated sample. For the heated samples, the shear strain was measured at room temperature using samples after each heating time had elapsed.

[0044] FIG. 5 is a diagram showing the rate of change of shear strain due to heating at 180°C. FIG. 6 is a diagram showing the rate of change of shear strain due to heating at 200°C. FIG. 7 is a diagram showing the change in the rate of change of shear strain of sample 1 with respect to heating time. FIG. 8 is a diagram showing the change in the rate of change of shear strain of sample 2 with respect to heating time. FIG. 9 is a diagram showing the change in the rate of change of shear strain of sample 3 with respect to heating time. In FIGS. 7 to 9, heating at 180°C is shown by diamonds, and heating at 200°C is shown by squares. In addition, the range of the rate of change from -0.15 to 0.15 is shown by dot hatching, and the range of the rate of change from -0.2 to 0.2 is shown by oblique hatching. Furthermore, the rate of change of shear strain after a heating time of 3000 hours is shown by a circle.

[0045] As shown in Figures 7 to 9, for all samples 1 to 3, the shear strain decreases almost linearly with time up to a heating time of 3000 hours. For sample 1, the rate of change in shear strain after heating at 180°C for 3000 hours was -0.071 (Figure 5), satisfying requirement [1] below. Additionally, for sample 1, the rate of change in shear strain after heating at 200°C for 3000 hours was -0.087 (Figure 6), satisfying requirement [2] below. Requirement [1] |(γ1-γ0) / γ0|≦0.15 Here, γ0 is the shear strain of the adhesive layer before heating, and γ1 is the shear strain after heating the adhesive layer at 180° C. for 3,000 hours. Requirement [2] |(γ2-γ0) / γ0|≦0.2 Here, γ0 is the shear strain of the adhesive layer before heating, and γ2 is the shear strain after heating the adhesive layer at 200°C for 3000 hours.

[0046] Sample 2 was heated at 180°C for 3000 hours, but the rate of change in shear strain was -0.204 (Figure 5), which does not meet the above requirement [1]. Sample 2 was also heated at 200°C for 3000 hours, but the rate of change in shear strain was -0.238 (Figure 6), which does not meet the above requirement [2].

[0047] Sample 3 was heated at 180°C for 3000 hours, but the rate of change in shear strain was -0.156 (Figure 5), which does not meet the above requirement [1]. Sample 2 was heated at 200°C for 3000 hours, but the rate of change in shear strain was -0.384 (Figure 6), which does not meet the above requirement [2].

[0048] In other words, even after heating Sample 1 at high temperatures of 180°C and 200°C for 3000 hours, the shear strain remains almost unchanged and there is almost no deterioration. In other words, Sample 1 has excellent heat resistance.

[0049] -Component analysis (ICP optical emission analysis) Using the above samples 1 and 2, a qualitative analysis was carried out by ICP emission spectrometry. Sample 1 contained 1500 ppm of phosphorus (P), while sample 2 contained less than the detection limit of phosphorus (P), i.e., less than 100 ppm.

[0050] As described above, Sample 1 satisfies the above requirements [1] and [2], and further satisfies the following requirements [3], [4], and [5]. Requirement [3] The adhesive is a silicone-based resin. Requirement [4] The amount of phosphorus (P) in the adhesive layer, as quantitatively analyzed by inductively coupled plasma (ICP) optical emission spectrometry using a high-frequency inductively coupled plasma (ICP) as a light source, is 100 ppm or more. Requirement [5] The adhesive layer contains 30% or more by volume of inorganic filler.

[0051] Samples 2 and 3 satisfy the above requirements [3] and [5], but do not satisfy the above requirements [1], [2], and [4]. These results confirmed that the adhesive layer containing 100 ppm or more of phosphorus (P) improves the heat resistance of the adhesive layer. As mentioned above, it is believed that phosphorus traps and deactivates radical species generated during the process of decomposing the resin due to heat, thereby suppressing the decomposition of the resin and improving the heat resistance of the adhesive. In addition to containing phosphorus, a method that can achieve a similar effect is to include components that are thought to have radical receptors on their surface, such as carbon black, acetylene black, and carbon nanotubes, in the adhesive layer or inorganic filler.

[0052] The present disclosure is not limited to the above-mentioned embodiments, etc., and can be realized in various configurations without departing from the spirit of the present disclosure. For example, the technical features in the embodiments corresponding to the technical features in each form described in the Summary of the Invention column can be appropriately replaced or combined in order to solve some or all of the above-mentioned problems or to achieve some or all of the above-mentioned effects. Furthermore, if a technical feature is not described as essential in this specification, it can be appropriately deleted.

[0053] The present disclosure can also be realized in the following application examples. [Application example 1] A holding device for holding an object, A plate-shaped portion formed in a plate shape; A base portion formed in a plate shape and supporting the plate-shaped portion; an adhesive layer disposed between the plate-shaped portion and the base portion, the adhesive layer including an adhesive and an inorganic filler, and bonding the plate-shaped portion and the base portion; Equipped with The adhesive layer is |(γ1-γ0) / γ0|≦0.15 is satisfied. holding device. Here, γ0 is the shear strain of the adhesive layer before heating, and γ1 is the shear strain of the adhesive layer after heating at 180° C. for 3000 hours. [Application example 2] The holding device according to Application Example 1, The adhesive layer is |(γ2-γ0) / γ0|≦0.2 is satisfied. holding device. Here, γ0 is the shear strain of the adhesive layer before heating, and γ2 is the shear strain of the adhesive layer after heating at 200° C. for 3000 hours. [Application example 3] The holding device according to Application Example 1 or Application Example 2, The adhesive is a silicone-based resin. holding device. [Application example 4] The holding device according to any one of Application Examples 1 to 3, The adhesive layer is characterized in that the amount of phosphorus (P) quantitatively analyzed by ICP emission spectrometry using a high-frequency inductively coupled plasma (ICP) as a light source is 100 ppm or more. holding device. [Application example 5] The holding device according to any one of Application Examples 1 to 4, The adhesive layer contains 30% by volume or more of the inorganic filler. holding device. [Explanation of symbols]

[0054] 10...Electrostatic chuck 20…Plate-shaped part 22...Adsorption electrode 24...Side 1 26…Second side 30…Base section 32... Coolant flow path 40...Adhesive layer 50…Gas supply line 52…Gas outlet 70...Test piece 80…Aluminum plate

Claims

1. A holding device for holding an object, A plate-shaped portion formed in a plate shape; A base portion formed in a plate shape and supporting the plate-shaped portion; an adhesive layer disposed between the plate-shaped portion and the base portion, the adhesive layer including an adhesive formed of a resin material and an inorganic filler, and bonding the plate-shaped portion and the base portion; Equipped with The adhesive layer is |(γ1-γ0) / γ0|≦0.15 is satisfied, The adhesive layer is characterized in that the amount of phosphorus (P) quantitatively analyzed by ICP emission spectrometry using a high-frequency inductively coupled plasma (ICP) as a light source is 100 ppm or more. holding device. Here, γ0 is the shear strain of the adhesive layer before heating, and γ1 is the shear strain of the adhesive layer after heating at 180° C. for 3000 hours.

2. 2. The holding device according to claim 1, The adhesive layer is |(γ2-γ0) / γ0|≦0.2 is satisfied. holding device. Here, γ0 is the shear strain of the adhesive layer before heating, and γ2 is the shear strain of the adhesive layer after heating at 200° C. for 3000 hours.

3. 2. The holding device according to claim 1, The adhesive is a silicone-based resin. holding device.

4. A holding device according to any one of claims 1 to 3, The adhesive layer contains 30% by volume or more of the inorganic filler. holding device.

Citation Information

Patent Citations

  • Bonding material and semiconductor supporting device

    JP2008218992A

  • Film adhesive for semiconductor vacuum processing equipment

    JP2011508419A

  • Member for semiconductor manufacturing device

    JP2014183077A

  • Part for semiconductor manufacturing device, and method for manufacturing the same

    JP2014207374A